1995
DOI: 10.1128/mcb.15.4.1968
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Homologous Recombination in Mammalian Chromosomes by Using the I-SceI System of Saccharomyces cerevisiae

Abstract: The mitochondrial intron-encoded endonuclease I-SceI of Saccharomyces cerevisiae has an 18-bp recognition sequence and, therefore, has a very low probability of cutting DNA, even within large genomes. We demonstrate that double-strand breaks can be initiated by the I-SceI endonuclease at a predetermined location in the mouse genome and that the breaks can be repaired with a donor molecule homologous with regions flanking the breaks. This induced homologous recombination is approximately 2 orders of magnitude m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
287
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(295 citation statements)
references
References 24 publications
4
287
0
1
Order By: Relevance
“…Expression of I-SceI stimulated HR by 155-fold, which is in good agreement with previously published results 4,8,30 28-31 , corresponding to 11% of transfected cells undergoing HR between the target locus and the repair plasmid. After transfection of the original ZFN expression vectors (WT-WT), the number of transfected cells after seven days was too low to assess the frequency of HR, probably due to high toxicity.…”
Section: Zfn Dimerization Variants Stimulate Hr-based Gene Repairsupporting
confidence: 92%
See 1 more Smart Citation
“…Expression of I-SceI stimulated HR by 155-fold, which is in good agreement with previously published results 4,8,30 28-31 , corresponding to 11% of transfected cells undergoing HR between the target locus and the repair plasmid. After transfection of the original ZFN expression vectors (WT-WT), the number of transfected cells after seven days was too low to assess the frequency of HR, probably due to high toxicity.…”
Section: Zfn Dimerization Variants Stimulate Hr-based Gene Repairsupporting
confidence: 92%
“…Several recent studies have reported gene-targeting frequencies of 1-18% HR events per 5 mammalian cell when the targeted DSB was introduced by natural or artificial endonucleases [2][3][4][5][6][7][8] . The ability to generate precise modifications of the genome -knockouts, mutations or corrections -within 1 in 100 to 1 in 5 cells presents this methodology as a potentially powerful tool for genetic studies, biotechnology and gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Substantial increases have been obtained by engineering double-strand breaks (DSBs) in the target locus, but this approach is not currently applicable to single-step targeting strategies. [11][12][13][14] Recent approaches to the problem have included the use of short fragments of DNA, 15 DNA/RNA oligonucleotides (reviewed in Ref. 16), modified selection conditions 17 and adeno-associated virus vectors 18 and these have generated some dramatically improved targeting efficiencies.…”
Section: Correspondence: Acg Porter This Paper Is Dedicated To the Mementioning
confidence: 99%
“…24 They can induce site-specific DSBs, and thereby stimulate homologous recombination of up to 10 000-fold in cultured cells. 25,26 MGNs were used to induce homologous recombination in a variety of cell types and organisms, including mammalian cells, mice, plants, Drosophila, Escherichia coli and trypanosome. 27,28 MGN-induced DSB can also be repaired by non-homologous end-joining (NHEJ), an error-prone process, which frequently results in micro-insertions or micro-deletions (indels) at the site of the break.…”
Section: Introductionmentioning
confidence: 99%